RNA-seq analysis of the whole transcriptome of MDA-MB-231 mammary carcinoma cells exposed to the antimetastatic drug NAMI-A1. Issue 10 (7th October 2015) - Bergamo, Alberta; Gerdol, Marco; Lucafò, Marianna; Pelillo, Chiara; Battaglia, Marilena; Pallavicini, Alberto; Sava, Gianni
<x xml:space="preserve">Abstract</x> Gene expression profiling has been introduced into drug development to understand the activity of chemical entities in pre-clinical settings.